2020
DOI: 10.1007/s12094-020-02391-x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic nicotine delivery systems (ECs) and COVID-19: the perfect storm for young consumers

Abstract: The COVID-19 pandemic caused a change in our society and put health systems in crisis worldwide. Different risk factors and comorbidities have been found that increase the risk of mortality when acquiring this infection. The use of alternative devices to the cigarette like the electronic cigarettes, the vapers have been studied widely and generators of great controversy since it has been discovered that they also produce different pulmonary affections. When developing the SARS-CoV2 infection, different theorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
7
0
7
Order By: Relevance
“…There are few data concerning the sole effect of nicotine (substitute treatments) and its interaction with the ACE. Studies on the effects of e-cigarettes' electronic nicotine delivery systems (e-cigarettes, vaping) on RAS are inconclusive and also lead to controversies ( Leung and Sin, 2020 ; Majmundar et al, 2020 ; Pino et al, 2020 ). Health providers in the US question whether the vaping epidemic might have contributed to the large amount of hospitalizations for COVID-19 among young individuals ( Pino et al, 2020 ).…”
Section: Results and Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few data concerning the sole effect of nicotine (substitute treatments) and its interaction with the ACE. Studies on the effects of e-cigarettes' electronic nicotine delivery systems (e-cigarettes, vaping) on RAS are inconclusive and also lead to controversies ( Leung and Sin, 2020 ; Majmundar et al, 2020 ; Pino et al, 2020 ). Health providers in the US question whether the vaping epidemic might have contributed to the large amount of hospitalizations for COVID-19 among young individuals ( Pino et al, 2020 ).…”
Section: Results and Observationsmentioning
confidence: 99%
“…Studies on the effects of e-cigarettes' electronic nicotine delivery systems (e-cigarettes, vaping) on RAS are inconclusive and also lead to controversies ( Leung and Sin, 2020 ; Majmundar et al, 2020 ; Pino et al, 2020 ). Health providers in the US question whether the vaping epidemic might have contributed to the large amount of hospitalizations for COVID-19 among young individuals ( Pino et al, 2020 ). Anyway, nicotinic acetylcholine receptor could play a key role in the pathophysiology of COVID-19 infection and might represent a target for the prevention and control of the disease ( Changeux et al, 2020 ).…”
Section: Results and Observationsmentioning
confidence: 99%
“…Recent systematic reviews have suggested a likely association between cigarette smoking and progression of COVID-19 infection to adverse outcomes ( Patanavanich & Glantz, 2020 ; Vardavas & Nikitara, 2020 ), although this relationship is still debated ( Lippi & Henry, 2020 ). There are few data on e-cigarette use and COVID-19 risk, although some have hypothesized that vaping might increase susceptibility to COVID-19 ( Kaur et al, 2020 ; Pino et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Um artigo publicado 30 sobre indivíduos que procuraram espontaneamente um setor de emergência do hospital Mount Sinai em Nova York com 21 a 50 anos de idade (i.e., proxy do subgrupo populacional da região servida pelo hospital e que não tinha problema de acesso ao serviço de saúde) e testaram positivo para Covid-19 encontrou que a população de fumantes tinha uma chance 80% maior de apresentar uma avaliação inicial por raio-x que a levava a ser internada por Covid-19 quando comparada à de não fumantes. Um pequeno detour sobre o tema da relação de populações mais jovens de fumantes com a Covid-19 sugere um aumento do olhar dos artigos publicados sobre a importância que os dispositivos eletrônicos para fumar (DEF) podem ter para esse subgrupo populacional 31,32 . Apesar de não haver ainda nenhum estudo que tenha medido a relação entre usar DEF e desfechos desfavoráveis de Covid-19, até mesmo pela ainda baixa proporção de adultos usuários de DEF, existe uma plausibilidade biológica apoiada, inclusive, em exemplos passados recentes da relação de uso de DEF com outras doenças respiratórias graves, de que esses usuários podem vir a seguir o mesmo exemplo dos fumantes de cigarros convencionais [31][32][33] .…”
Section: Vieses De Seleção E Informação Diferenciais Entre Fumantes Eunclassified
“…Um pequeno detour sobre o tema da relação de populações mais jovens de fumantes com a Covid-19 sugere um aumento do olhar dos artigos publicados sobre a importância que os dispositivos eletrônicos para fumar (DEF) podem ter para esse subgrupo populacional 31,32 . Apesar de não haver ainda nenhum estudo que tenha medido a relação entre usar DEF e desfechos desfavoráveis de Covid-19, até mesmo pela ainda baixa proporção de adultos usuários de DEF, existe uma plausibilidade biológica apoiada, inclusive, em exemplos passados recentes da relação de uso de DEF com outras doenças respiratórias graves, de que esses usuários podem vir a seguir o mesmo exemplo dos fumantes de cigarros convencionais [31][32][33] .…”
Section: Vieses De Seleção E Informação Diferenciais Entre Fumantes Eunclassified